Public vs. private schooling as a route to universal basic education: A comparison of China and India - SMITH, William C. (Institutional Knowledge at Singapore Management University, 2016)
This article examines whether focusing primarily on public schooling can lead to more rapid achievement of universal basic education (UBE) than relying on a mixture of public and private schooling. Through a structured, focused comparison, we find China's greater emphasis on public schooling has contributed to higher enrollment, attendance, graduation rates, gender parity, and proportion of students entering higher education than India, the country with the world's largest private sector in primary and secondary education. This comparison suggests that greater emphasis on public schooling in developing countries may lead to more rapid UBE attainment than encouraging privatization.